Effectiveness of Intensive Short-term Dynamic Psychotherapy on Attachment Styles, Somatization, and Health Anxiety in Patients with Chronic Pain - Nakhaei Moghadam, Roksana; Bahrainian, Seyed Abdolmajid; Nasri, Maryam (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The experience of long-term pain and beliefs related to time associated with pain are key factors in understanding the experience of pain and psychological distress in patients. Intensive Short-term Dynamic Psychotherapy (ISTDP) can play an effective role in improving psychological symptoms. Therefore, this study aimed to determine the effectiveness of ISTDP on attachment styles, somatization, and health anxiety in patients with chronic pain.Methods and Materials: This quasi-experimental study employed a pre-test, post-test, and follow-up design with a control group. The study population consisted of all patients with chronic pain visiting pain clinics in Tehran in 2023. Thirty participants were randomly and conveniently selected and allocated into experimental (15 participants) and control (15 participants) groups. The experimental group received fifteen 90-minute sessions of ISTDP, while the control group received no intervention. Both groups were assessed for attachment styles, somatization, and health anxiety. Data were analyzed using a two-way analysis of variance with repeated measures.Findings: Before the intervention, the mean scores for secure attachment, somatization, and health anxiety were 72.25, 58.36, and 24.08 in the treatment group, and 72.12, 59.16, and 23.52 in the control group, respectively (p < .05). After the intervention, the treatment group showed a significant increase in the mean scores of secure attachment and significant decreases in avoidant and anxious attachment styles, health anxiety, and somatization compared to the control group (p < .001).Conclusion: The results of this study indicate that ISTDP significantly improves the psychological symptoms examined in the experimental group. With caution, the use of this intervention as an adjunct treatment in patients with chronic pain is recommended.